Comparing the yield components of three most popular commercial watermelon cultivars in Kenya with one newly introduced cultivar and one landrace - Gichimu, Bernard M.; Owuor, B.O; Dida, M. M. (Academic Journals, 2009)
High yield is a major goal for watermelon (Citrullus lanatus) breeders. The objective of this study was to compare the yield components of some watermelon accessions available in Kenya and to identify high yielding accession(s) for recommendation to Kenyan growers and for use in breeding programs. A field trial involving five cultivated watermelon accessions in Kenya namely ‘Sugarbaby’, ‘Crimson Sweet’, ‘Charleston Gray’, ‘Yellow Crimson’; and one local landrace (GBK-043014) from Kakamega district in Western Kenya, was conducted at Maseno University Research Fields between September 2007 and May 2008. The experiment was laid out in a Randomized Complete Block Design with three replications. Data was collected on yield and yield components of the accessions and subjected to analysis of variance using SAS version 9.1. Differences were declared significant at 5% level based on Least Significant Difference. The landrace demonstrated the highest yield potential while ‘Yellow Crimson’ which is a newly introduced commercial cultivar performed much better compared to other commercial cultivars. Selection of desirable traits in these accessions has priority for the future breeding programs. ‘Yellow Crimson’ was also recommended to Kenyan growers as the commercial cultivar with highest yield potential.
Keywords: Yield potential; watermelon; commercial cultivars; landrace; Kenya